Place of Birth and Cognitive Function among Older Americans: Findings from the Harmonized Cognitive Assessment Protocol - Zhuoer Lin; Xi Chen (Global Labor Organization (GLO), 2024)
Growing evidence suggests that place of birth (PoB) and related circumstances may have long-lasting and multiplicative contributions to various later-life outcomes. This study investigates the extent to which PoB contributes to a wide range of domains of later-life cognitive function. Leveraging a nationally representative sample of older Americans from the Health and Retirement Study (HRS), cognitive function is assessed in Harmonized Cognitive Assessment Protocol (HCAP). Regression-based Shapley decompositions are employed to quantify the contribution of PoB. We show that PoB significantly contributes to all assessed cognitive domains including memory, executive function, language and fluency, visuospatial function, orientation, and general cognitive function. Geographic disparities in cognitive function are evident across PoB, with individuals born in US southern states and foreign-born individuals performing worse than those born in other states. Overall, state of birth accounts for 2.2-9.7% of the total variance in cognition after controlling for age, sex, and race/ethnicity, which declines to 2.0-7.0% after further controlling for comprehensive socioeconomic and health factors over the life course, and are robust to the control of current state of residence. Addressing these disparities requires more equalized place-based policies, resources, and early-life environments to promote health equity over the life course.
Keywords: I14; I10; J13; J14; H75; 330; Geographic disparities; Health equity; Cognitive domains; Life course; Early-life circumstances